42 Beacon Street, ca. 1865-70 - Unknown (Tufts Archival Research Center, 2005)
Street-level view of southern facades of buildings from 41-46 Beacon Street looking south-southwest from Walnut Street towards Spruce Street. Buildings in this view are opposite the Boston Common. Building in the center of image is the Somerset Club. A wall adorns the front of the Somerset Club building. There is a street lamp in front of 41 Beacon Street. In 1872 The Somerset Club moved to this location which was the former mansion of Colonel David Sears. Built by Alexander Parris. 8 3/8 x 7 overall 9 13/16 x 8 3/8 Photographs